DIACHRONY OF THE EPIC PATTERN: “ATTACK ON THE WEDDING PROCESSION” - D. Delić, Lidija (Philological Studies, 2019)
In a diachronic perspective, from the oldest recordings of oral epics in the Balkans (Erlangen manuscript, tentatively emerged in the third decade of the eighteenth century; Bogišićʼs volume, which integrates manuscripts from the Adriatic coast from late XVII until the second half of the eighteenth century – to the published collections and manuscripts of Vuk Karadžić, and Sarajlijaʼs Pjesmarica) this paper traces the transformation of the archaic syuzhet model “attack on the wedding procession”. The author also points out the divergence of the epic pattern depending on the protagonist type (haiduks – uskoks), which is interpreted within the context of haiduks’ epical domains, inherited from supernatural beings who inhabit the mountain (a chthonic place) and rule over that (symbolic) space.